DEVELOPING PROFESSIONAL COMPETENCE OF FUTURE PROFESSIONALS ON THE BASIS OF CULTURAL APPROACH - Safarova Rohat Gaybullaevna (Galaxy International Interdisciplinary Research Journal, 2022)
The following article deals with the substantiation of the need for a purposeful formation of the professional competence and cultural approach of future teachers in organizing cultural practices, as a mandatory variable form of organizing the educational activities of students in accordance with the requirements of the state educational standard of education.The formation of the professional competence of future teachers based on cultural approach is considered as an organized, meaningfully rich process of purposeful assistance to the formation of professional competence in the educational process of the University taken together of its main components - motivational-value, cognitive, and technological.The results of the study helped to form the author's view of the process of forming the professional competence of future teachers in the organization of cultural practices of schoolchildren based on a cultural approach.